Analisis Perbedaaan Volume Kendaraan pada Jam Puncak Sore Hari di Simpang Wirolegi Melalui Uji One-Way ANOVA Berbasis SPSS - Yoga Alvian Pratama; Amri Gunasti (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study focuses on the analysis of traffic density in Jember City, particularly at the Wirolegi Intersection, which is known to have a high density level. This condition often triggers congestion that hinders public mobility, so that appropriate and data-based handling efforts are needed. The purpose of this study is to identify and analyze the level of density at critical congestion points through a statistical approach using the One Way ANOVA method. The research method used is quantitative descriptive with a descriptive observational approach. Primary data was collected directly through a field survey in 2025 at the Wirolegi Intersection as one of 3 intersections in Jember City. The data obtained were then processed using normality tests, homogeneity tests, and One Way ANOVA with the help of SPSS software. The results of the analysis show that the traffic flow density on the three routes studied, namely Jalan Gunung Haryono, Jalan Brigjen Katamso, Jalan Yos Sudarso, does not show a significant difference. The significance value of the ANOVA test is greater than 0.05 which indicates the similarity of density levels between routes. Further testing (post hoc testing) also strengthens this finding. The conclusion of this study shows that handling congestion at the Wirolegi Intersection needs to be done comprehensively through traffic control and evaluation of the transportation system to improve smoothness and mobility in Jember City.